2023
DOI: 10.1002/anie.202300531
|View full text |Cite
|
Sign up to set email alerts
|

Parahydrogen‐Induced Polarization of a Labeled, Cancer‐Targeting DNA Aptamer

Abstract: Enhancing NMR signals of biomacromolecules by hyperpolarization offers exciting opportunities for diagnostic applications. However, their hyperpolarization via parahydrogen remains challenging as specific catalytic interactions are required, which are difficult to tune due to the large size of the biomolecule and its insolubility in organic solvents. Herein, we show the unprecedented hyperpolarization of the cancer-targeting DNA aptamer AS1411. By screening different molecular motifs for an unsaturated label i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Finally, the hyperpolarized ligand is released. The vast majority of PHIP research concentrates on the efficient hyperpolarization of molecules and their applications; notably, the hyperpolarization of molecular systems, which can be employed in medical diagnostics or catalysis [25–31] . Although one might suppose that all about o‐H 2 NMR is already known, it has recently been observed that hyperpolarized o‐H 2 can be produced from p‐H 2 during the hPHIP process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the hyperpolarized ligand is released. The vast majority of PHIP research concentrates on the efficient hyperpolarization of molecules and their applications; notably, the hyperpolarization of molecular systems, which can be employed in medical diagnostics or catalysis [25–31] . Although one might suppose that all about o‐H 2 NMR is already known, it has recently been observed that hyperpolarized o‐H 2 can be produced from p‐H 2 during the hPHIP process.…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of PHIP research concentrates on the efficient hyperpolarization of molecules and their applications; notably, the hyperpolarization of molecular systems, which can be employed in medical diagnostics or catalysis. [25][26][27][28][29][30][31] Although one might suppose that all about o-H 2 NMR is already known, it has recently been observed that hyperpolarized o-H 2 can be produced from p-H 2 during the hPHIP process. Additionally, what is more interesting is that the hyperpolarized o-H 2 manifests as an antiphase signal, and is known as the Partially Negative Line (PNL) effect.…”
mentioning
confidence: 99%
“…The first alkyne-linked compound was already published in 1976, accompanied by new synthesis methods in the following years [24][25][26][27]. With the discovery of potential antiviral properties and other synthetic opportunities, alkyne-linked derivatives remained an integral part of research to the present day [28][29][30][31][32][33][34][35]. However, the main methods known so far are to substitute uracil either only at position 6 or at position 5 [26][27][28][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%